Sports video analysis for player strength and weakness psychiatry in the context of object-relational data bases - Uma, Maheswari; Rajaram, M.; Sivanandam, S.N. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.